2009
DOI: 10.1007/s11262-009-0331-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of an Indian isolate of Banana bunchy top virus based on six genomic DNA components

Abstract: Banana bunchy top virus (BBTV) is a single-stranded circular DNA virus of the genus Babuvirus, belonging to family Nanoviridae. The six genomic DNA components of Indian (Lucknow) isolate of BBTV were amplified by polymerase chain reaction (PCR) with specific primers using total DNA extracted from banana tissues showing typical symptoms of banana bunchy top disease (BBTD). The resulting ~1.1 Kb amplicons were cloned and sequenced. Analysis of sequence data revealed the presence of six full-length components of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 27 publications
6
25
0
Order By: Relevance
“…All the six components of HB-TN isolate clustered with isolates of the South Pacific group and the isolates of Asian group clustered as separate clade. Our results corroborated with the results of Vishoni et al [19] who have reported that the BBTV isolate occurring in Lucknow, North India was belong to the South Pacific group. The species demarcation criteria for nanoviruses was based on amino acid identities of the CP gene and the members of distinct species should be \85% similarity (Vetten et al 18).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…All the six components of HB-TN isolate clustered with isolates of the South Pacific group and the isolates of Asian group clustered as separate clade. Our results corroborated with the results of Vishoni et al [19] who have reported that the BBTV isolate occurring in Lucknow, North India was belong to the South Pacific group. The species demarcation criteria for nanoviruses was based on amino acid identities of the CP gene and the members of distinct species should be \85% similarity (Vetten et al 18).…”
Section: Resultssupporting
confidence: 93%
“…In India, BBTV has been prevalent since 1943 and so it is possible that genetic variability such as that observed among isolates of the Asian group exists. Recently, the complete genomes of BBTV isolates occurring in Pakistan [1] and Lucknow, North India [19] were reported and found to belong to the South Pacific group.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, all six components of BBTV-K isolate were evaluated. Sequence analysis of BBTV-K isolate revealed that it is as similar as other reported genomes of BBTV [41]. Burns et al [10] demonstrated that the genome of BBTV comprises at least five ssDNA components based on the restriction digests of putative full-length clones synthesized from purified virions.…”
Section: Discussionsupporting
confidence: 53%
“…Based on phylogenetic analysis of DNA-R, Karan et al [26] divided BBTV isolates into two groups such as a PIO group and South-East Asian (SEA) group. BBTV isolates from India were found to be belonging to the PIO group [6,37,41]. Similarly, Amin et al [3] characterized the Pakistan (Sindh) isolate of BBTV by analyzing of sequences of DNA components and indicated that BBTV present in Pakistan belongs to the PIO group.…”
Section: Introductionmentioning
confidence: 99%
“…1). BBTV is widely distributed in banana growing countries in the Asia, Pacific region (Australia, China, Guam, India, Pakistan, Sri Lanka, Hawaii, Indonesia, Japan, the Philippines, Taiwan, Tonga, Samoa and Vietnam) and in a few countries in Africa (Egypt, Gabon, Angola and Burundi) [2,16,50,89,99]. There are many other banana growing regions, South and Central America, the Caribbean, Papua New Guinea, Thailand and in many countries in African and Asia, where BBTV has not been confirmed [43,89].…”
Section: Geographical Distributionmentioning
confidence: 99%